The Commission of Conservation as a Forerunner to the National Research Council 1909-1921 - Girard, Michel (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1991)
AbstractThis paper links the history of the Canadian Commission of Conservation (1909-1921) to the creation of the National Research Council through the fight between the two organizations for federal funds in scientific research. In my view, the Commission of Conservation (or COC) was abolished in 1921 because it persisted in advocating conservation, an expression of early 20th century environmentalism, in a world which was no longer interested in this issue.